Short‐term intra‐individual variation of urinary biomarkers in dogs with stable chronic kidney disease. (11th January 2023) - Chen, Hilla; Maron, Lotem; Segev, Gilad
Abstract: Background: Active‐ongoing kidney damage is present in animals with stable chronic kidney disease (CKD), as reflected by biomarkers in urine. Interpretation of serial messurements of biomarkers requires knowledge of its intra‐individual variation. Aims: To evaluate the short‐term intra‐individual variation of urinary neutrophil gelatinase‐associated lipocalin and kidney injury molecule‐1 (uNGAL, uKIM‐1, respectively) in dogs with stable CKD, and to determine whether normalization to urinary creatinine (uCr) decreases variation. Animals: Twenty‐five dogs with naturally‐occurring stable CKD. Methods: Prospective, observational study. Dogs were diagnosed with CKD based on the International Renal Interest Society guidelines. Dogs were included only if the variation in serum creatinine concentration was <25% on at least 2 measurements during the 3 months preceding inclusion, and only if serum creatinine variation was <20% during the 14‐day study period. Urine samples were collected on days 0, 4, 10 and 14. uNGAL and uKIM‐1 were measured using ELISA. Results: The median coefficients of variation (CV) of uNGAL and uNGAL/uCr were 42% (range, 7%‐127%), and 44% (range, 8%‐100%), respectively, and the CV 90th percentiles were 97% and 83%, respectively. The median CV of uKIM‐1 and uKIM‐1/uCr were 29% (range, 16%‐91%), and 23% (range, 6%‐76%), respectively, and the CV 90th percentiles were 56% and 52%, respectively. Conclusions and Clinical Importance: Changes of >100% and >60% for uNGAL and uKIM‐1, respectively, in serial measurements are higher than the normal expected variation and therefore might indicate need for further investigation for underlying causes of kidney damage.